2016
DOI: 10.1007/s00394-016-1202-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 supplementation using an oral spray solution resolves deficiency but has no effect on VO2 max in Gaelic footballers: results from a randomised, double-blind, placebo-controlled trial

Abstract: Purpose Vitamin D inadequacy is a global health concern in athletes as well as the general population. Whilst the role of vitamin D in skeletal health is well defined, there remains uncertainty over whether vitamin D supplementation has an added benefit beyond bone health.MethodsThis randomised placebo-controlled trial in healthy male and female Gaelic footballers (n = 42) investigated the effect of vitamin D3 supplementation [3000 IU (75 µg) daily for 12 weeks, via an oral spray solution] on VO2 max which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 82 publications
7
49
0
3
Order By: Relevance
“…Furthermore, muscular strength did not change across the seasons and concurs with findings from Close et al (21) . Parallel to this, there was no improvement in physical parameters following supplementation in Irish university Gaelic footballers (29) with a lower mean vitamin D status than our baseline and previous authors at 47·4 and 43·1 nmol/l for their intervention and placebo groups, respectively. Although we did not supplement our cohort with vitamin D, it is still comparative for baseline measurements, specifically as both aforementioned were the only UK-based cohorts to our knowledge in this young adult population.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, muscular strength did not change across the seasons and concurs with findings from Close et al (21) . Parallel to this, there was no improvement in physical parameters following supplementation in Irish university Gaelic footballers (29) with a lower mean vitamin D status than our baseline and previous authors at 47·4 and 43·1 nmol/l for their intervention and placebo groups, respectively. Although we did not supplement our cohort with vitamin D, it is still comparative for baseline measurements, specifically as both aforementioned were the only UK-based cohorts to our knowledge in this young adult population.…”
Section: Discussionsupporting
confidence: 55%
“…The analysis conducted in this study formed part of a double‐blind, randomized, placebo‐controlled trial which took place at the University of Ulster Coleraine between November 2014 and April 2015 (Todd et al., ). All procedures were approved by the University Research Ethics Committee (REC/14/0087), registered at http://www.clinicaltrials.gov (NCT02278172) and conducted in accordance to the declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Gaelic footballers signed informed consent and attended appointments to obtain fasted blood samples. Physical measures were taken before and after a 12‐week intervention, the detailed methods of which have been reported previously (Todd et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A relative study examined the association between vitamin D status and maximalintensity exercise performance in junior and collegiate hockey players and showed that if vitamin D status is causally related to maximal-intensity exercise performance in athletes, the effect size is likely small [20]. A study evaluated the Vitamin D supplementation in Gaelic players and showed that there was no significant effect on maximal VO2, skeletal muscle or lung function [42]. …”
mentioning
confidence: 99%